Anaerobic digestion for biomethane production from food waste pretreated by enzymatic hydrolysis - Deb, Nibedita; Alam, Md. Zahangir; Rahman, Tawfkur; Jami, Mohammed Saedi; Mansor, Mariatul Fadzillah; Ahmad Tajuddin, Husna (Academic Research Publishing Group, 2023)
Food waste (FW) is one of the main problems in the world due to the continuous increase in the global population. Anaerobic digestion (AD) of FW was an alternative and economical solution to develop an effective method to enhance biomethane (BioM) production that uses enzyme pretreatment and hydrolysis of FW by locally produced cellulase and amylase enzymes. In this study, two types of sources fungi (TNAF-1 to TNFA-3) and (TNBC-1 to TNBC-3) strains were isolated from animal feed and compost. The cellulase and amylase activities were 300U/mL & 400U/mL, respectively. Based on OFAT results obtained, optimization of three factors such as pH of 5, TS of 12.5% (V/V) and enzyme loading of 80U/mL was carried out by applying the FCCCD under the RSM to develop a second-order regression model successful improvement in the production of reducing sugar of 162mg/mL was achieved. However, biogas yield was optimum using OFAT parameters such as the biogas inoculum of 25%, pH of 7, AD digestion times of 29 days, 500mL of hydrolysate food waste and room temperature at 30°C (±2). The results show the biogas contained was found such %3 hydrogens, 57% methane and 40% carbon dioxide. The new fungi are very potential for upgrading the biogas of BioM that is non-toxic as well as biodegradable, and therefore may be encouraging to the water treatment plants in future applications.